Arabidopsis photoperiodic regulator CONSTANS feeds back to control the circadian clock - San Martín, Abril (2024)
Human beings live in a world defined by daily cycles of light and darkness caused by the Earth’s rotation around its axis. Plants, like most living organisms, have evolved internal circadian clocks that time biological processes in anticipation of these daily environmental changes (Young and Kay, 2001). The plant clock relies on core genes encoding transcription factors (TFs), which regulate each other’s expression through intricate networks of interlocking transcriptional-translational feedback loops (Nohales and Kay, 2016). These loops ultimately control the expression of thousands of genes, allowing plants to adapt to daily fluctuations in light, temperature, and humidity (Covington et al., 2008). In addition to daily rhythms, the Earth experiences yearly seasonal cycles marked by longer, warmer days in spring and summer, followed by shorter, cooler days in autumn and winter. Seasonal changes in day length and temperature intensify with distance from the equator. Consequently, the ability of plants to adjust their growth and development in anticipation of seasonal changes determines their latitudinal distribution (McMillan, 1960).